2014
DOI: 10.5466/ijoms.12.216
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Immunohistochemical Studies of the Distribution of Elastic Fibers in Oral Fibrous Hyperplasia

Abstract: Oral fibrous hyperplasias (OFH) are thought to result from hyperplasia of collagen fibers.However, details regarding the presence of elastic fibers and reticular fibers other than collagen fibers in OFH are unclear.Therefore, this study focused on elastic fibers in the connective tissue with regard to OFH, and assessed the histopathological, histochemical, and immunohistochemical distribution of the elastic fibers.All cases of OFH (120 cases) were performed Elastica van Gieson (EvG) staining, and the distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…CD34 positivity was observed in the spindle cells constituting OFH accompanied by elastic fibers, and undifferentiated mesenchymal cells around myogenic blood vessels near the lesion were related to the formation of a part of elastic fibers that constituted OFH. It has also been reported that CD34-positive spindle cells participate in the formation of elastofibroma [18]. CD34 is a 110kDa single-chain trans-membrane glycoprotein and is expressed on immature haematopoietic stem/ progenitor cells, capillary endothelial cells, and embryonic fibroblasts).…”
Section: Discussionmentioning
confidence: 97%
“…CD34 positivity was observed in the spindle cells constituting OFH accompanied by elastic fibers, and undifferentiated mesenchymal cells around myogenic blood vessels near the lesion were related to the formation of a part of elastic fibers that constituted OFH. It has also been reported that CD34-positive spindle cells participate in the formation of elastofibroma [18]. CD34 is a 110kDa single-chain trans-membrane glycoprotein and is expressed on immature haematopoietic stem/ progenitor cells, capillary endothelial cells, and embryonic fibroblasts).…”
Section: Discussionmentioning
confidence: 97%